Literature Review: A Historical Study of Digital Media Da'wah Research as A Religious Movement - Marzal, Novrizon; Haryanti , Erni (Alfuad: Jurnal Sosial Keagamaan, 2025)
Digital da'wah has become one of the important phenomena in the world of Islamic da'wah in the modern era. This article explores trends in digital da'wah research in Indonesia through a historical approach, using the garuda.kemdikbud.go.id database for the period 2019-2024. The results of the study show a significant increase in the number of articles discussing digital da'wah, especially during the COVID-19 pandemic, which forced a transition from conventional da'wah to digital platforms. Social media such as TikTok and Instagram, as well as podcast formats, have become popular tools for spreading Islamic values, especially among the millennial generation. This study also highlights challenges such as competition with non-religious content and limited digital literacy among da'wah practitioners. However, the opportunities for digital da'wah are vast, enabling personalized messaging and a wide audience reach. With technological advancements like augmented reality (AR) and virtual reality (VR), the future of digital da'wah is expected to be even brighter. This article makes an important contribution to understanding the transformation of digital da'wah and paves the way for further research.